Tingkat Stres Kerja Pada Perawat di Unit Rawat Inap RSUD Labuang Baji Makassar - Rufaedah Amir, Astrid Pratiwi; Salam, Jumhur; Anas, M.; Ishak, Syamsul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The work demands of nurses in supervising, monitoring the health conditions of patients and the large number of patients in certain parts of a hospital require the ability of nurses to be ready to be placed in any unit with a workload that can continue to increase, which can cause work stress for nurses. This study aims to determine the level of work stress among nurses in the inpatient unit of Labuang Baji Hospital, Makassar. The research design used a cross sectional approach and the Bianchi stress questionnaire. The sample in this study was all 45 nurses in the inpatient room. Data analysis used the chi square method. The results showed that controlling had a relationship with the level of work stress of nurses p value = 0.114 (p ≤ 0.05), organizing had a relationship with the level of work stress of nurses p value = 0.000 (p ≤ 0.05), nursing care had a relationship with the level of nurse work stress p value = 1.000 (p ≤ 0.05), the work environment has a relationship with the nurse's work stress level p value = 0.125 (p ≤ 0.05). The conclusion of this study shows that nurses have good interpersonal relationships, there is no relationship between controlling, nursing care, and the work environment with the nurse's work stress level, while the organizing element has a relationship with the nurse's work stress level.